Former à évaluer des compétences en enseignement supérieur : un dispositif d’évaluation novateur - Nathalie Michaud; Martin Roy (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In a course existing since a few years, the purpose of this development research (Harvey & Loiselle, 2009) is to improve the evaluation system which allows to judge the competency to evaluate of teachers in training. The origin of the project comes from a desire to bond in a more rigorous and coherent way the teaching – assessment sequence within the course. This article aims to document the development of the innovative evaluation system put in place. The selected frameworks to develop the new system are explained. Furthermore, some data obtained from a survey filled by students are presented regarding the operationalization of the system.